2016
DOI: 10.1523/jneurosci.0313-16.2016
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling Representations of Object and Grasp Properties in the Human Brain

Abstract: The properties of objects, such as shape, influence the way we grasp them. To quantify the role of different brain regions during grasping, it is necessary to disentangle the processing of visual dimensions related to object properties from the motor aspects related to the specific hand configuration. We orthogonally varied object properties (shape, size, and elongation) and task (passive viewing, precision grip with two or five digits, or coarse grip with five digits) and used representational similarity anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
74
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(93 citation statements)
references
References 60 publications
11
74
1
Order By: Relevance
“…First, the hand shape selective area may indeed occupy a small area of PPC, most likely AIP. Although several fMRI studies indicate the hand shape selective area includes beyond AIP such as SMG, the whole IPS, and SPL (Fabbri et al, 2016;Króliczak et al, 2016;Ariani et al, 2015), AIP is consistently found to take part in the special encoding of hand shape Binkofski et al, 1998;Klaes et al, 2015), which has been demonstrated in this work as well ( figure 3). Therefore, since SEEG electrodes are randomly distributed within the whole PPC, it is reasonable that only a small percentage of them presented gesture selective.…”
Section: Ppc Assists Gesture Decodingsupporting
confidence: 60%
See 2 more Smart Citations
“…First, the hand shape selective area may indeed occupy a small area of PPC, most likely AIP. Although several fMRI studies indicate the hand shape selective area includes beyond AIP such as SMG, the whole IPS, and SPL (Fabbri et al, 2016;Króliczak et al, 2016;Ariani et al, 2015), AIP is consistently found to take part in the special encoding of hand shape Binkofski et al, 1998;Klaes et al, 2015), which has been demonstrated in this work as well ( figure 3). Therefore, since SEEG electrodes are randomly distributed within the whole PPC, it is reasonable that only a small percentage of them presented gesture selective.…”
Section: Ppc Assists Gesture Decodingsupporting
confidence: 60%
“…Intracortical electrical stimulation to lateral region of monkey's area 5 within PPC elicits finger and wrist movements (Rathelot et al, 2017). Functional magnetic resonance imaging (fMRI) studies reveal that grip type (power vs precision grasp) is encoded in several subareas of PPC (Fabbri et al, 2016;Di Bono et al, 2015). In addition to objectrelated grasp, other intransitive hand gestures like scissor-rock-paper can also be decoded from PPC, as demonstrated by another fMRI study (Dinstein et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rather, dorsal object-representations are unique from those in ventral cortex in several fundamental respects. First, object processing in dorsal cortex follows an overarching posterior-to-anterior visual-to-motor gradient, with more posterior areas (such as CIP) dedicated predominantly to analysis of visual properties such as 3-D curvature, while anterior areas (such as AIP) are increasingly concerned with computations related to potential motor interactions with the stimulus, such as encoding the object’s absolute object location in egocentric space, reaching trajectory, and hand preshaping (Culham and Valyear, 2006; Fabbri, Stubbs, Cusack, & Culham, 2016; Shmuelof and Zohary, 2005; Stark & Zohary, 2008). In fact, this visual-to-motor gradient may not be limited to the rostro-caudal axis, but may also extend along a medio-lateral axis as well, reflecting the underlying connectivity patterns with the visual and motor cortices (Freud et al, 2016; Kravitz et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…A related consideration is how best to depict these actions in order to probe underlying neural responses at a meaningful level of abstraction. Historically, researchers have relied on highly-controlled action stimuli (Jastorff et al, 2010;, often sampling primarily from hand actions such as reaching or hammering (Watson & Buxbaum, 2014;Fabbri et al, 2016;Wurm et al, 2017). However, these welldesigned and controlled stimuli are fundamentally limited in the range of actions they depict, which in turn constrains researchers' ability to discover joints in the broader domain of action perception.…”
mentioning
confidence: 99%